[(18) F]FDG-PET imaging is an early non-invasive pharmacodynamic biomarker for a first-in-class dual MEK/Raf inhibitor, RO5126766 (CH5126766), in preclinical xenograft models - Tegnebratt, Tetyana (Springer, 2013)
BACKGROUND: Positron emission tomography (PET) with [2-(18) F]-2-fluoro-2-deoxy-D-glucose ([(18) F]FDG-PET) was acquired at multiple time-points a) to monitor the early response to RO5126766 (CH5126766) in xenograft models b) to evaluate non-invasive small animal [(18) F]FDG-PET imaging as a biomarker for MEK inhibitors for translation into dose-finding studies in cancer patients and c) to explore the underlying mechanism related to FDG uptake in tumors treated with RO5126766. METHODS: [(18) F]FDG uptake was studied in HCT116 (K-ras), COLO205 (B-raf) mutants and COLO320DM (wild type) xenografts from day 0 to 3 of RO5126766 treatment using a microPET Focus 120 and complemented with in vitro incubations, ex-vivo phosphor imaging and immunohistochemical (IHC) analyses. RESULTS: In the HCT116 (K-ras) and COLO205 (B-raf) mutant xenografts, significant decreases in [(18) F]FDG uptake were detected in vivo on day 1 with 0.3 mg/kg and ex vivo on day 3 with 0.1 mg/kg RO5126766. [(18) F]FDG changes correlated with decreases in tumor cells proliferation (Ki-67) and with changes in expression levels of GLUT1. No effects were observed in drug resistant COLO320DM cells. The cellular fractionation and Western blotting analyses suggested that the change of [(18) F]FDG uptake associated with RO5126766 is due to translocation of GLUT1 from membrane to cytosol, similar to the results reported in the literature with EGFR tyrosine kinase inhibitors, which also target the MAPK pathway. CONCLUSIONS: RO5126766 inhibition resulted in a rapid time - and dose - dependent decline in [(18) F]FDG uptake in both mutant xenografts. These results strongly resemble the clinical observations obtained with MEK/Raf inhibitors support the use of preclinical [(18) F]FDG-PET as a translational tool for decision support in preclinical and early clinical development of MEK inhibitors.